2006
DOI: 10.1038/sj.cr.7310005
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting gene-virotherapy of cancer

Abstract: Our purpose is to completely elimination of xenograft tumor in animal tumor model in order to work out a protocal for the cure of patient. Gene therapy and viral therapy for cancer have got some therapeutic effects, but both have no great breakthrough. Therefore, we worked out a new strategy called Targeting Gene-Virotherapy of Cancer which is a combination of the advantage of gene therapy and virotherapy. This new strategy has stronger antitumor effect than either of them alone. A tumor specific replicative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
(6 reference statements)
0
19
0
Order By: Relevance
“…Traditional replication-defective adenovirus cannot target tumor cells, which limits its therapeutic value. Replication selective virotherapy holds great promise for the treatment of cancer [7-9] whose appealing features include tumor-selective targeting, viral self-spreading in cancer cells, and no cross-resistance to current treatments. One strategy to achieve tumor specificity is the use of tumor- or tissue-specific promoters, such as MUC1, PSA, or PS2, to drive adenoviral genes that are essential for replication [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional replication-defective adenovirus cannot target tumor cells, which limits its therapeutic value. Replication selective virotherapy holds great promise for the treatment of cancer [7-9] whose appealing features include tumor-selective targeting, viral self-spreading in cancer cells, and no cross-resistance to current treatments. One strategy to achieve tumor specificity is the use of tumor- or tissue-specific promoters, such as MUC1, PSA, or PS2, to drive adenoviral genes that are essential for replication [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we adopted the Gene-Viro-Therapy (CTGVT) approach of cancer targeting, as it has demonstrated much higher anti-tumor effects [42, 43]. Many reports have shown that TRAIL could induce the selective death in a wide range of human cancer cells [4446].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers have used TRAIL as a foreign gene for cancer treatment in CTGVT research [4749]. Although all of those treatments were effective when tested in vivo in nude mouse xenografts by IT injection [42, 43, 50], these studies did not carry out the animal experiments with IV injection of the vector, and such data are necessary for clinical evaluation. Furthermore, CTGVT research tended to show effective treatment of hepatic carcinoma but without discussing the problem of liver enrichment if the vector needs to be used to target other tissues [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of oncolytic viruses has been identified as a novel potential strategy for cancer treatment owing to its capacity to destroy tumor cells both in vitro and in vivo with minimal collateral damage to normal cells [6]. In recent decades, a number of oncolytic virus vectors have been developed with mutations in genes associated with virulence or viral DNA synthesis to confine viral replication to cancer cells and avoid causing disease [7,8]. One approach to engineering replication selectivity is the deletion of viral genes, which causes inefficient viral replication in normal cells but expansion in tumor cells.…”
Section: Introductionmentioning
confidence: 99%